FANATISME MADZHAB DALAM TAFSIR AL AL-KASYAF - iklima, Ima (Program Studi Ilmu Al-Qur'an dan Tafsir, Universitas Islam Negeri Datokarama Palu, 2024)
The Qur'an has a general nature and requires deeper explanations. The flexibility in interpreting the Qur'an results in an ever-changing interpretation process over time and place. Schools of thought and scholarly affiliations also influence the approach of interpreters in interpreting the Qur'an. One famous tafsir is Al-Kasysyaf by Az-Zamakhsyari, known for its beautiful use of vocabulary and its connection to the Mu'tazilah. The Mu'tazilah emphasize the concepts of monotheism, justice, promises, and threats in their interpretations. Based on its methodology, this study is a literature review (library research) since the data sources are primarily books and literature related to the research topic, including the works of al-Zamakhshary and other relevant sources. This paper discusses the fanaticism of Zamakhsari in interpreting his tafsir, particularly in the interpretation of the attributes of Allah. Zamakhsari adopts the views of the Mu'tazilah, who deny the mortality of Allah and interpret words such as